A Databris: Accounting for Living-While-Circumcised during the Shoah in the Audiovisual Archive - Geller, Jay (Holocaust and genocide studies, 2025)
In Nazi-occupied Europe, even with authentic identity documents, linguistic fluency, knowledge of Christian prayers and practices, and "Aryan" appearance, Jewish male anatomy was destiny: a Jew, bearing the singular mark of (male) Jewish difference, circumcision, was ever at risk. Situations that threatened the exposure of that difference, efforts to avoid such situations, and responses when such situations became unavoidable play a significant role in survivor testimony and memoir literature. Yet to date, there has been no extensive scholarly study of the manifold ways in which circumcision impacted Jewish survival. After indicating the necessity to undertake the first comprehensive study of this crucial constraint on Jewish survival during the Shoah, this research note addresses the difficulties faced in pursuing such research in the audiovisual archive and in codifying the data. It then suggests how to resolve these issues to more fully display and reckon with how living-while-circumcised affected the many forms of life and modes of death, alongside the resilience and resourcefulness, the fear and fatalism, of Jews during the Shoah.